2006
DOI: 10.4315/0362-028x-69.5.1072
|View full text |Cite
|
Sign up to set email alerts
|

PCR Primers for the Detection of Staphylococcal Enterotoxins K, L, and M and Survey of Staphylococcal Enterotoxin Types in Staphylococcus aureus Isolates from Food Poisoning Cases in Taiwan

Abstract: Staphylococcal enterotoxins (SEs) are important causative agents in gastroenteritidis and food poisoning cases. They are serologically grouped into five major classical types, i.e., SEA, SEB, SEC, SED, and SEE. In addition, new SEs, such as SEG through SEM, have recently been identified and characterized. In an attempt to survey the distribution of classical and new SEs in organisms responsible for staphylococcal infections in Taiwan, we developed PCR primers for the genes that define the SEK, SEL, and SEM typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 30 publications
3
25
0
Order By: Relevance
“…However, the predominance of pulsotypes (A, B, C, and I) that harbor SE genes supports the theory that superantigenic toxins are important for pathogenesis of the udder (5,15). In our study, the seg + sei combination, with or without other genes, was the most prevalent (48.9%) and was often detected in strains isolated from cases of food poisoning (6,8,42). The involvement of staphylococcal enterotoxin H in staphylo coccal food poisoning has been proposed because it was detected in foods responsible for two outbreaks (23,25).…”
Section: Discussionmentioning
confidence: 80%
“…However, the predominance of pulsotypes (A, B, C, and I) that harbor SE genes supports the theory that superantigenic toxins are important for pathogenesis of the udder (5,15). In our study, the seg + sei combination, with or without other genes, was the most prevalent (48.9%) and was often detected in strains isolated from cases of food poisoning (6,8,42). The involvement of staphylococcal enterotoxin H in staphylo coccal food poisoning has been proposed because it was detected in foods responsible for two outbreaks (23,25).…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, as described earlier, staphylococcal diseases related to SAg, such as foodpoisoning and TSST-1, may result from a complex phenotype caused by multiple toxins (Orwin et al, 2001). Considering this data, however, it should be reminded that S. aureus strains with high isolation frequency and high enterotoxin productivity does not mean that these strains cause a high number of food-poisoning cases or outbreaks (Cihang et al, 2006).…”
Section: Discussionmentioning
confidence: 93%
“…However, 6 S. aureus strains with the tst gene were detected without sec and sell, because the latter are encoded on SaPI2 (Novick et al, 2010). Cihang et al (2006) analysed S. aureus isolates from foodpoisoning cases in Taiwan and found strains were positive for at least one SE or tst gene. Our results showed that SaPI4 did not contain any superantigen gene and this finding is in full agreement with Argudin et al (2010) and Novick et al (2010).…”
Section: Discussionmentioning
confidence: 98%
“…The PCR mixture consisted of 0.25 µl of primer 1 (100 pmol /µl), 0.25µl of primer 2 (100 pmol/µl), 2 µl of deoxynucleoside triphosp hate (2.5 mmol/liter), 2.5 µl of 10 x thermophilic buffer, 1. [25] d [26] Germany) with the program shown in Table 1.…”
Section: Detection Of Enterotoxigenicitymentioning
confidence: 99%